External Morphological Study of Aporiacrataegi (Linnaeus, 1758), (Lepidoptera: Pieridae). Northern Iraq - Mouhannad M. Aljaf (Journal of Global Pharma Technology, 2018)
This work was included external morphological study of male Black veined white butterfly Aporiacrataegi L. 1758. The study involved morphological characters of many body regions, in addition the male genitalia. This morphological characters study supported by illustrations, it should be noted the work specimens were collected from northern Iraq.Keywords: Butter fly, Lepidoptera, Pieridae, Aporia, Description.